The theological turn in youth ministry - Root, Andrew, 1974-; Dean, Kenda Creasy, 1959- (Downers Grove, Ill. : IVP Books, 2011)
Andrew Root and Kenda Creasy Dean invite us to envision youth ministries full of practical theologians, addressing the deep questions of life with a wonderfully adolescent mix of idealism, cynicism and prophetic intolerance for hypocrisy. The result is a more rigorous and meaningful youth ministry, and a more theologically grounded and engaged church.
Part 1 : theological starting points : what does youth ministry have to do with theology? -- The new rhetoric of youth ministry / Kenda Creasy Dean -- God is a minister : youth ministry as fundamentally theological / Andrew Root -- Youth ministry as an integrative theological task : toward a representative method / Andrew Root -- Proclaiming salvation : the ministry of youth for the twenty-first-century church / Kenda Creasy Dean -- Walking into the crisis of reality : how theology is constructed / Andrew Root -- Youth ministry as discerning Christopraxis : a hermeneutical model / Andrew Root -- God's hiddenness, absence and doubt / Andrew Root -- Part 2 : theology enacted : exploring youth ministry practice -- Is Jesus magic? : healing and the cross in youth ministry / Andrew Root -- Talking about sin with young people / Andrew Root -- Holding on to our kisses : the hormonal theology of adolescence / Kenda Creasy Dean -- The eschatological significance of summer camp / Kenda Creasy Dean -- What are we doing in these mountains? : the outdoor trip and the theology of the cross / Andrew Root -- The mission trip as global tourism : are we ok with this? / Andrew Root -- Doubt and confirmation : the mentor as co-doubter / Andrew Root -- Ascension deficit disorder : youth ministry as a laboratory for hope / Kenda Creasy Dean -- Postscript : reflecting on method : youth ministry as practical theology / Andrew Root with Blair D. Bertrand.
Title from PDF title page (viewed on Jan. 6, 2014).
Includes bibliographical references.
Added to collection customer.56279.3
Keywords: Church work with youth; Theology -- Miscellanea; RELIGION -- Christian Life -- General; RELIGION -- Christian Ministry -- Adult; RELIGION -- Christian Ministry -- Counseling & Recovery; Church work with youth; Theology; Electronic books; Miscellanea